Community Legal Protection in Obtaining Comprehensive and Quality Health Information and Education - Rani Tiyas Budiyanti; Roro Isyawati Permata Ganggi; Murni Murni (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
Based on the 7th article Law of the Republic of Indonesia Number 36/2009 on Health, everyone has the right to receive balanced and responsible health information and education. Even so, there are problems that still occur in the community such as unequal access to health information and unequal valid health education, especially in rural and coastal areas. This research aims to describe the government’s responsibility and the solutions that can be done in fulfilling the right to access health information. This research was normative research with a statutory and comparative approach using primary, secondary, and tertiary legal materials. The Indonesian government has a responsibility to fulfill the health information and education right based on the 17th article of Law of the Republic of Indonesia Number 36/2009 on Health. Several strategies can be done such as sector collaboration, building information system support facilities, provision of valid health portals, and allocation of budgeting related to health information and education.